(untitled) (American Journal of Islam and Society, 2019)
The true measure of success for any written work is the attention it receives from its readers; the publication of subsequent editions is one such marker. The first publication of Jonathan Brown’s critically acclaimed textbook on ḥadīth placed the complex domain and vast tradition of Prophetic ḥadīth works, perhaps for the very first time, at the center of lay English readership. At long last, a work existed that bridged the deep gulf between contemporary academic studies and traditional Islamic scholarship, especially considering that nowhere is this rift deeper than in the field of ḥadīth studies. His work was appreciated across a variety of circles across faith and sectarian lines, and now the publication of the second edition bears testimony to the success it truly deserves.